1999
DOI: 10.1046/j.1440-1819.1999.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

The Noh mask test for analysis of recognition of facial expression

Abstract: A preliminary study on the Noh mask test for analysis of recognition of facial expression was performed. The present study was conducted on 15 normal subjects (mean age: 32 years, SD 9.7 years) as the first step to test for the differences between psychiatric patients and normal subjects. Stimuli were created by photographs of 15 Noh masks at different vertical angles. Subjects were given 12 tasks (12 emotion items), and each task consisted of 15 trials (15 Noh mask images). In each trial, the subject viewed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…These results show trends opposite to the rules of Noh, consistently with the previous findings using vertically tilted Noh mask images [4][6], [9]. The present data thus suggest comparable effect of tilting angles, by simply manipulating the shadows of the Noh mask images.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results show trends opposite to the rules of Noh, consistently with the previous findings using vertically tilted Noh mask images [4][6], [9]. The present data thus suggest comparable effect of tilting angles, by simply manipulating the shadows of the Noh mask images.…”
Section: Discussionsupporting
confidence: 92%
“…In Experiment 1, shadows extracted from happy and sad faces of the Noh masks significantly imposed happier and sadder impressions to the otherwise neutral-faced masks, respectively. Similarities and differences between four different types of masks are noteworthy, because a large part of the preceding studies involved only a single type of the mask [4][6]. The effect of shadows were overall similar for all types of Noh masks, even though the happy conditions regarding Koomote and Doji seem to have reflected a ceiling effect.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, lip corners seen from above and below appear to be drawn upwards (as if being happy) and downwards (as if being sad), respectively. Minoshita et al [8] also confirmed these findings by analyzing larger numbers of emotional categories. For example, downward tilted masks were recognized as happier, more composed, and less surprised, compared with upward tilted masks (see also [9][10]).…”
Section: Introductionmentioning
confidence: 73%
“…Given that artists have been creating masks for many thousands of years from cultures all around the world, it is surprising that almost no scientific research evaluating the perception of emotion from masks has been conducted to date. Some studies [10][11] have investigated the perception of emotion from Japanese Noh masks, but there is nothing else. In the study by Minoshita et al [10], participants viewed images of a single Noh mask presented at a variety of orientations (face oriented up or down by various degrees) and were required to indicate, yes or no, for each image whether the mask appeared "sad", "surprised", or "happy".…”
Section: Introductionmentioning
confidence: 99%